Financial Capability, Financial Threat, and Health: Implications for Social Work Practice - Sally A Hageman; Edward Pecukonis (Journal of Financial Therapy, 2021)
Interest in financial capability and financial threat has gained momentum in social work. However, little is known about the relationship between an individual’s financial capability and perception of financial threat with self-reported health scores. This study examines connections between financial capability, financial threat, and self-reported health scores. Primary data was collected via a paper and pencil survey yielding responses from 153 adults ages 18 and older. Respondents primarily came from the east coast of the United States. Results indicate lower Financial Threat Scores (FTS) are significantly correlated with better self-reported health scores. Regression results reveal FTS is a significant predictor of self-reported health, b = -0.59, t(126) = -7.46, p < 0.001. Financial capability score is not significantly associated with self-reported health. Results may inform social work practice.
Keywords: financial capability; financial threat; self-reported health; money and health